The sociology of Islam: secularism, economy and politics - Johnston, David L.; Tamney, Joseph B.; Anjum, Ovamir; Zoli, Corri; Pace, Enzo; Woodlock, Rachel (Ithaca, 2011)
Keskin, Tugrul: The Sociology of Islam. - S. 1-18 Part: Islam, economy and politics Ozaral, Basak: Islam and moral economy. - S. 21-44 Anjum, Ovamir: Has modernity ruptured Islamic political tradition? - S. 45-60 Hendrick, Joshua D.: Neo-liberalism and 'third way' Islamic activism : Fethullah Gillen and Turkey's new elite. - S. 61-90 Amin, Husnul: From Islamism to post-Islamism : the coming of a new intellectual trajectory in Pakistan. - S. 91-126 Part: Globalization and Islam Zoli, Corri: The multicultural 'Ummah'. - S. 129-152 Reddig, Melanie: Power struggle in the religious field of Islam : modernization, globalization and the rise of Salafism. - S. 153-176 Johnston, David L.: Yusuf al-Qaradawi and Chandra Muzaffar : how theology impacts reformist views on Islam and secularism. - S. 177-200 Walton, Jeremy F.: Civil Islam, means and end of liberal piety : ethnographic notes from among Turkey's charitable foundations. - S. 201-226 Part: Muslim society in the West Górak-Sosnowska, Katarzyna: Indigenous and immigrant faces of Islam in Poland Katarzyna Gorak-Sosnowska. - S. 229-246 Moosavi, Leon: Muslim converts and islamophobia in Britain. - S. 247-268 De Castro, Cristina Maria: Islam in Brazil : reflections on economic life and religiosity in a minority context. - S. 269-290 Pace, Enzo; Frisina, Annalisa: Italian secularism revisited? : Muslims' claims in the public sphere and the long struggle towards religious equality. - S. 291-315 Part: Islam and muslim societies Ogungbile, David Olu: Tradition and response : Islam and muslim societies. - S. 319-342 Tamney, Joseph B.: Religion-state relations in Malaysia. - S. 343-376 Ziadeh, Radwan: The islamist movement in Syria : historical, political and social struggle. - S. 377-394 Woodlock, Rachel: Many hijabs : interpretative approaches to the questions of Islamic female dress. - S. 395-418 Kusujiarti, Siti: Pluralistic and informal welfare regime : the roles of islamic institutions in the Indonesian welfare regime. - S. 419-452 Schellenberg, Kathryn; Daassa, Mohamed: What they say about the treatment of expatriate workers in the United Arab Emirates. - S. 453-486